Implementation of Ubudiyyah Activities to Instill Religious Values in Santri (Students) at Islamic Boarding School - Christin Widyastutia; Baharudin Baharudin; Rudy Irawan (At-Ta'lim : Media Informasi Pendidikan Islam, 2025)
ENGLISH: Implementation of Ubudiyyah Activities to Instill Religious Values in Santri (Students) at Islamic Boarding SchoolObjective: This study aims to describe the implementation of ubudiyah activities among female students at Al-Hikmah Islamic Boarding School in Bandar Lampung and to analyze the factors that support and hinder the internalization of religious values. Method: This study employs a descriptive qualitative approach, utilizing observation, interviews, and documentation. Data were analyzed using an interactive model that included reduction, presentation, and conclusion drawing, with validity reinforced through triangulation. Results: Ubudiyah activities are carried out in a structured manner through the habit of performing obligatory and sunnah worship, such as congregational prayers, tadarus, zikr, and dhuha prayers. Supporting factors include the exemplary behavior of the asatidzah, consistent supervision, and well-organized pesantren management. Obstacles include uneven student motivation and limited worship facilities. Conclusion: Ubudiyah activities play a strategic role in shaping the religious behavior of santri, although their effectiveness is influenced by motivation and the availability of facilities. Contribution: This research contributes to a theoretical and practical review of studies on Islamic education related to religious guidance strategies based on worship habits in Islamic boarding schools, focusing on instilling religious values in santri. Keywords: Ubudiyah activities; Islamic religious values; Students (Santri); Islamic boarding schoolINDONESIAN: Penerapan Kegiatan Ubudiyyah untuk Penanaman Nilai-Nilai Religius Santri di Pondok PesantrenTujuan: Penelitian ini bertujuan mendeskripsikan penerapan kegiatan ubudiyah pada santri putri di Pondok Pesantren Al-Hikmah Bandar Lampung serta menganalisis faktor pendukung dan penghambat internalisasi nilai religius. Metode: Penelitian menggunakan pendekatan kualitatif deskriptif melalui observasi, wawancara, dan dokumentasi. Data dianalisis dengan model interaktif yang meliputi reduksi, penyajian, dan penarikan kesimpulan, dengan validitas diperkuat melalui triangulasi. Hasil: Kegiatan ubudiyah dilaksanakan secara terstruktur melalui pembiasaan ibadah wajib dan sunnah, seperti shalat berjamaah, tadarus, dzikir, dan shalat dhuha. Faktor pendukung mencakup keteladanan asatidzah, pengawasan konsisten, dan manajemen pesantren yang tertata. Hambatan meliputi motivasi santri yang belum merata serta keterbatasan sarana ibadah. Kesimpulan: Kegiatan ubudiyah berperan strategis dalam membentuk perilaku religius santri, meskipun efektivitasnya dipengaruhi oleh motivasi dan fasilitas. Kontribusi: Kontribusi penelitian ini sebagai tinjauan teoritis dan praktis kajian kajian tentang pendidikan Islam terkait strategi pembinaan religius berbasis pembiasaan ibadah di pesantren dalam meenanamkan nilai-nilai religius santri.